2023
DOI: 10.3389/fcell.2023.1130823
|View full text |Cite
|
Sign up to set email alerts
|

The versatile roles of ADAM8 in cancer cell migration, mechanics, and extracellular matrix remodeling

Abstract: The posttranslational proteolytic cleavage is a unique and irreversible process that governs the function and half-life of numerous proteins. Thereby the role of the family of A disintegrin and metalloproteases (ADAMs) plays a leading part. A member of this family, ADAM8, has gained attention in regulating disorders, such as neurogenerative diseases, immune function and cancer, by attenuating the function of proteins nearby the extracellular membrane leaflet. This process of “ectodomain shedding” can alter the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…ADAM8 has been reported to be highly expressed in pancreas cancer ( Schlomann et al, 2015 ; Yu et al, 2020 ) or ductal adenocarcinoma ( Jaworek et al, 2021 ), is coupled to poor clinical prognosis of cancer and seems to be linked to the effect of chemoresistance to medical treatment of cancers ( Conrad et al, 2019 ). Based on all these findings, it can be assumed that ADAM8 plays a role in cancer cell migration, such as breast cancer cell migration ( Mierke, 2023 ). Therefore, we revealed that the motility of ADAM8 knock down MDA-MB-231 human breast cancer cells and ADAM8-Ctrl MDA-MB-231 cells in 3D collagen matrix scaffolds is altered.…”
Section: Discussionmentioning
confidence: 99%
“…ADAM8 has been reported to be highly expressed in pancreas cancer ( Schlomann et al, 2015 ; Yu et al, 2020 ) or ductal adenocarcinoma ( Jaworek et al, 2021 ), is coupled to poor clinical prognosis of cancer and seems to be linked to the effect of chemoresistance to medical treatment of cancers ( Conrad et al, 2019 ). Based on all these findings, it can be assumed that ADAM8 plays a role in cancer cell migration, such as breast cancer cell migration ( Mierke, 2023 ). Therefore, we revealed that the motility of ADAM8 knock down MDA-MB-231 human breast cancer cells and ADAM8-Ctrl MDA-MB-231 cells in 3D collagen matrix scaffolds is altered.…”
Section: Discussionmentioning
confidence: 99%
“…A disintegrin and metalloproteinases (ADAMs) and ADAMs with thrombospondin motifs (ADAMTS) are key protease families involved in ECM remodeling; ADAMs modulate cell-ECM interactions and signal transduction through the cleavage of cell surface molecules, while ADAMTS specifically target ECM components such as proteoglycans and collagens, directly contributing to ECM structural changes and functional dynamics. For instance, ADAM8 indirectly contributes to the breakdown and restructuring of the ECM by regulating MMP9 expression, orchestrating the dynamic interplay between these crucial components in ECM remodeling [ 27 , 28 ]. Additionally, other tissue proteases, such as serine, aspartic, and cysteine proteases, also play significant roles in ECM remodeling [ 29 ].…”
Section: The Key Factors For Regulating Ecm Remodelingmentioning
confidence: 99%
“…For instance, according to the mechanisms of tumor cell migration and invasion, ADAM proteinases may direct cell migration through the shedding of cell adhesion molecules or modifying of cell-matrix interaction. Potential substrates involved in cell migration have been summarized in previous reviews [ 58 , 59 ]. Similarly, molecules like ADAM17 have a great number of substrates and are involved in diverse diseases and pathological processes.…”
Section: Link Between Substrate Cleavage and Biological Processes In ...mentioning
confidence: 99%